2017
DOI: 10.20473/fmi.v53i4.7161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemotherapy Response and Adverse Effects of Double-Platinum Plus Egfr-Tki Versus Double-Platinum Alone on NSLCLC Patients With Disease Progression and Egfr-Tki Treatment

Abstract: ABSTRAK EGFR-TKI adalah terapi lini pertama untuk pasien mutan EGFR. Namun, pasien akan mengalami perkembangan penyakit KKE/I/2017). Hasil penelitian menunjukkan bahwa karakteristik subjek antara dua lengan berbeda secara signifikan (p=0,05). Mutasi EGFR yang paling umum adalah ekson 21 (50% pada lengan A dan 60% pada lengan B). Uji kuadrat diuji pada parameter respon subyektif (EQ5D (p=0,483)). Sampel bebas T2 diuji pada parameter semi subyektif (berat badan (p=1.00)). Uji EGFR-TKI is the first-line therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…This is consistent with research in Wulandari, 2017, which is the subject of research in general women and the age range of 50 years. 1,8,9 This research subject is NSCLC patients who undergo positive EGFR mutation and patients dominate smokers than non-smokers. This is not following the IPASS study found that lung adenocarcinoma predominantly occurs in nonsmokers than smoker.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with research in Wulandari, 2017, which is the subject of research in general women and the age range of 50 years. 1,8,9 This research subject is NSCLC patients who undergo positive EGFR mutation and patients dominate smokers than non-smokers. This is not following the IPASS study found that lung adenocarcinoma predominantly occurs in nonsmokers than smoker.…”
Section: Discussionmentioning
confidence: 99%
“…Its study result also has the same with previous research, whre a group of nonsmokers patients tends to have positive EGFR mutation. 1,2,10 Smoking is the cause of 85-90% of all lung cancer cases. , SVCS (4%), dysphagia (2%), wheezing and stridor (2%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations